Eigenmannia besouro, a new species of the Eigenmannia trilineata species-group (Gymnotiformes: Sternopygidae) from the rio São Francisco basin, northeastern Brazil - Peixoto, Luiz Antônio W.; Wosiacki, Wolmar B. (Zootaxa, 2016)
A new species of the Eigenmannia trilineata species-group is described from the rio São Francisco basin, Brazil. It is distinguished from closely related species by a unique set of characters, including a subterminal mouth, the presence of ii,13–14 pectoral-fin rays, a coronomeckelian bone that is 30% the length of Meckel’s cartilage, the specific pattern of the dentition of the premaxilla and dentary, and the more anterior origin of the superior midlateral stripe. Comments on species of the E. trilineata species-group are presented.